Digital Kultur: Music and Cultural Festivals Platform of Performing Arts in Digital Era - Ranti Rachmawanti (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2022)
This article discusses the results of research on the development of the Digital Kultur application as a platform for organizing cultural festivals. The purpose of this research is to find out the development indicators that can be used in applications. Digital Kultur is an invention in the form of an application made for organizing various cultural festivals in Indonesia. It is designed to be one of the solutions to address technological challenges in the world of music and performing arts. Digital Kultur has made it easy for participants to compete, perform and express their abilities in music not only within a small event, but also in a large-scale cultural festival, involving dance, folklore, and other art fields. By using this application, festival participants are managed online, starting from the registration process, auditions, judgment, up to the result before the final offline festival. Participants will perform live and record through the application of Digital Kultur in any city or place, respectively, with the specification of facilities and infrastructure adapted to the conditions of the local area. The selection and assessment process is carried out directly, and only selected participants as finalists will be invited to perform directly at the festival venue. The main point of using this application is the effectiveness and efficiency of the operational time of the festival.